2011
DOI: 10.4103/0975-7406.80769
|View full text |Cite
|
Sign up to set email alerts
|

Prospective encounter study of the degree of adherence to patient care indicators related to drug dispensing in Health Care facilities: A Sri Lankan perspective

Abstract: The World Health Organization-recommended patient care indicators in Government Hospitals were assessed in 422 patients attending the Outpatient Department in selected hospitals of the Galle district in Southern Province. The average dispensing time (ADT), percentage of drugs actually dispensed (PDAD), percentage of drugs adequately labeled (PDAL) and patient's knowledge on correct dosage (PKCD) were compared in these selected teaching hospitals (TH), general hospitals (GHs) and district hospitals (DHs) in Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…In this study, the proportion of the drug-related problems that were resolved was significantly higher in the intervention group than the control group, which also has been shown in other studies 5 , 23 , 24 . While one can assume that resolution of drug-related problems during the inpatient stay may have improved individual patient outcomes, our study was not powered to demonstrate this outcome.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, the proportion of the drug-related problems that were resolved was significantly higher in the intervention group than the control group, which also has been shown in other studies 5 , 23 , 24 . While one can assume that resolution of drug-related problems during the inpatient stay may have improved individual patient outcomes, our study was not powered to demonstrate this outcome.…”
Section: Discussionsupporting
confidence: 76%
“…Lack of provision of patient information on safe medication administration at discharge is a common problem within the Sri Lankan hospital system 23 . This intervention directly addressed this gap as an intervention pharmacist provided both verbal and written medication information to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists do not currently work at a ward level in collaboration with medical teams in government hospitals in Sri Lanka. They predominantly undertake a supply and dispensing function with minimal interaction with doctors and little provision of information to patients and carers . In 2006, the Sri Lankan government introduced new Bachelor of Pharmacy degree courses in order to develop a workforce capable of providing additional clinical services.…”
Section: Discussionmentioning
confidence: 98%
“…Patients' poor understanding of medicines taken prior to hospital admission could be explained by poor labelling (often lacking name, strength and dose instructions) as previously described in a Sri Lankan public hospital which showed that inadequate drug labelling, inadequate explanation of dosage regimen, precautions and clinically important side effects correlated with poor patient knowledge of correct medicine doses …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation